Tribal Inclusive Ecotourism: Policy Recommendations to Boost Ecotourism in Chhattisgarh - Navin T.; Angel Protim Dutta (Journal of Social Responsibility, Tourism and Hospitality, 2023)
The present paper examines Chhattisgarh’s potential for tribal inclusive ecotourism particularly in the Bhoramdeo Wildlife Sanctuary. A variety of research techniques are used in this study, including structured surveys, interviews, group discussions, and literature reviews. Important discoveries emphasize how little the indigenous tribal populations participate in ecotourism. In order to solve this, the paper makes policy proposals that include building partnerships, improving infrastructure, promoting local culture, and increasing community awareness. By promoting tribalinclusive ecotourism, these policies hope to foster local community development, economic expansion, and ecological restoration.